Role of Talent Development on Talent Engagement and Self-Efficacy: A Structural Model - Ali, Mohammad; Ullah, Muhammad Shariat; Guha, Souman (Journal of Social Economics Research, 2020)
The purpose of this research is to examine the influence of talent development (TD) on talent engagement (TE) and self-efficacy (SE). Data were collected through a questionnaire from the trainees of Bangladesh Institute of Human Resource Management (BIHRM). Two hypotheses were developed and tested on the collected data. Structural equation modeling (SEM) is performed which includes both measurement model and structural model. Average variance extracted (AVE), Cronbach’s alpha (α), composite reliability (CR) and factor’s loading have been shown under the measurement model whereas path diagram is used to present the relationship among the constructs under the structural model. The results of the study support that talent development has significant impact on both talent engagement and self-efficacy of talented employees. The outcome of the study is highly consistent with the previous literature and the results have strong logical argument. The research implies that organizations should emphasize to improve knowledge and abilities of the talents which foster more attachment and conviction towards jobs as well as enhance the level of talents’ self-efficacy.